Social constructions of environmental services in a rapidly densifying peri-urban area under dual governance in Durban, South Africa - Sutherland, Catherine; Sim, Vicky; Buthelezi, Sibongile; Khumalo, Duduzile (African Biodiversity & Conservation, 2016)
Background: Biodiversity plays a critical role in improving the quality of life and resilience of poor urban communities in Durban.Objectives: However, the rapid densification that is taking place in the ‘rural periphery’ of the city is impacting significantly on the integrity of ecosystems, which provide valuable ecosystem services. It is also changing the relations between people and the environment. Mzinyathi and eSkebheni, in the north-west of Durban, are peri-urban areas located on Ingonyama Trust land and hence they are governed by both the traditional authority and the eThekwini Municipality.  The settlement pattern is changing rapidly here as middle and upper income residents move into the area, changing the way of life from being rural and ‘traditional’ to urban and ‘modern’.Method: This paper focused on the nexus of rapid urban growth, dual governance systems, biodiversity loss and cultural change in these two areas. It adopted a qualitative methodology and social constructivist approach. Data on the value of environmental services in the area was collected through interviewing the traditional authority, provincial and municipal planners and environmentalists, and household members.Results: The paper revealed that environmental services are constructed in multiple ways within a particular socio-historical and political context, that they have value to peri-urban communities, and that their function and use is changing as a result of the ‘modernisation’ of the area. The impact of the dual governance system and traditional land allocation process on environmental services is significant. This has implications for long term sustainability, for the quality of life of peri-urban residents and for planning and urban governance.